ANALYSIS LEGAL FRAMEWORK, RESOURCES AND OTHER PROCESSES AND RESPONSIBILITIES IN THE FORMAL VOCATIONAL EDUCATION AND TRAINING IN THE REPUBLIC OF NORTH MACEDONIA - Dokmanovikj, Misho ; Spasevski, Darko; Shapkova Kocevska, Katerina; Gichevska, Sanja (Education for Employment in North Macedonia (E4E@mk), 2018)
The team of the Institute for Strategic Research and Education(link is external) (ISIE) was engaged by E4E@mk Project to conduct an analysis of the current situation and the challenges with a special focus on the legal framework, the resources and other processes and competences within the formal vocational education. The analysis is based on empirical research conducted in the period August - October 2018. This document covers: research methodology (the instruments used for data collection and the respondents, the timeframe of the research and the data analysis); a brief statistical overview of the the situation in 2017 (the year before the launch of the project) in the secondary VET in the regions, schools and sectors of particular interest for the project; the main findings and recommendations related to the legal framework for vocational education and training and the findings related to the financing of VET (sources, amount, legal framework, resources, their distribution and use).